2014
DOI: 10.1101/sqb.2014.79.024810
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Decisions and Free Will: Empirical Results and Philosophical Considerations

Abstract: Spontaneous actions are preceded by brain signals that may sometimes be detected hundreds of milliseconds in advance of a subject's conscious intention to act. These signals have been claimed to reflect prior unconscious decisions, raising doubts about the causal role of conscious will. Murakami et al. (2014. Nat Neurosci 17: 1574-1582 have recently argued for a different interpretation. During a task in which rats spontaneously decided when to abort waiting, the authors recorded neurons in the secondary motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The neurons of the primary motor cortex greatly contribute to initiating movements [33]. At the same time, it is suggested that the decision to initiate movement originates in the dorsolateral prefrontal cortex [42] [43], depending also on the interaction with posterior parietal cortex and other areas of frontal cortex [44] [33].…”
Section: A Human Sensorimotor Skill Communication Systemmentioning
confidence: 99%
“…The neurons of the primary motor cortex greatly contribute to initiating movements [33]. At the same time, it is suggested that the decision to initiate movement originates in the dorsolateral prefrontal cortex [42] [43], depending also on the interaction with posterior parietal cortex and other areas of frontal cortex [44] [33].…”
Section: A Human Sensorimotor Skill Communication Systemmentioning
confidence: 99%